Efisiensi Penggunaan Tempat Tidur Berdasarkan Grafik Barber Johnson Di Rumah Sakit Jantung Diagram Depok - Indah, Fenita Purnama Sari; Andriati, Riris; Hanifa, Annisa Amalia; Maulina, Fresty Cahya; Ferdhani, Felinda Putri (EDU RMIK Jurnal Edukasi Rekam Medis Ilmu Kesehatan, 2025)
The efficiency od bed use can be seen through the Barber Johnson Chart, where the chart contains an efficiency area that can displays four inpatient indicators BOR (Bed Occupancy Rate), AvLOS (Average Length Of Stay), TOI (Turn Over Interval), and BTO (Bed Turn Over). The Barber Johnson chart itself has several benefits, namely to monitor the progress of achieving efficiency targets for bed use between units within a certain period, monitoring the impact of implementing a policy on the efficiency of bed use. The purpose of this research is to determine the efficiency of bed use based on Barber Johnson indicators for the 2023 period at the Diagram Hearth Hospital Depok. The type of research used is descriptive quantitative using observation and survey methods. The population in this study is a recapitulation of the inpatient census per room in January – December for the 2023 period. Sampling technique used is total sampling with saturated sampling. Research results of this research obtained the calculation results of the BOR value (35,89%), AvLOS value (1,97 days) and BTO (66,49 times). The BOR AvLOS, TOI and BTO indicator values are inefficient. Based on the results of the interpretation of the Barber Johnson Graph, the Barber Johnson point at the Depok Hearth Hospital Diagram in one year is beyond efficiency with a BOR value of 35,89% which is not at the efficiency point, according to the standard Barber Johnson Graph it must reach 75-85%. And the BTO value is 66,49 times, which is the BTO point that is inefficient, according to the Barber Johnson Chart it must reach 30-50 times.